The effect of varying gas headspace to meat ratio on the quality of pork loin stored in high O2 modified atmosphere. Issue 2 (3rd April 2017) - Marcinkowska-Lesiak, Monika; Poławska, Ewa; Półtorak, Andrzej; Wierzbicka, Agnieszka
ABSTRACT: A comparison was made of the effect of different gas headspace to meat ratio on quality of pork loin (m. longissimus thoracis et lumborum) obtained from crossbred pigs (Polish Landrance x Duroc, n = 6) as a function of cold storage. Samples were stored in modified atmosphere packs (80% O₂:20% CO₂) with gas headspace to meat ratios (G/M) of 3:1, 1:1 and 1:3. Physicochemical and microbiological parameters were monitored for up to 12 days. The results indicated that the best properties of meat were obtained when stored pork loins with the gas headspace to meat ratio of 1:1. G/M = 1:3 contributed to the increase in the growth of microorganisms and G/M = 3:1 and led to unfavorable changes in meat color. Finally, chemical properties of pork loins were unaffected ( P > 0.05) by varying the gas headspace to meat ratio.